Severe asthma in the era of COVID-19 - Gaspar-Marques, João (2021)
Funding Information: João Gaspar Marques has received research grants from AstraZeneca and honorarium as speaker/consultant from AstraZeneca, Novartis, Sanofi and TEVA. Mafalda van Zeller has received honorarium as speaker/consultant from AstraZeneca, GlaxoSmithKline, Novartis and TEVA. Pedro Carreiro Martins has received research grants from AstraZeneca and honorarium as speaker/consultant from AstraZeneca, GlaxoSmithKline, Novartis and Sanofi. Cláudia Chaves Loureiro has received honorarium as speaker/consultant from AstraZeneca, GlaxoSmithKline, Novartis, Sanofi and TEVA. Publisher Copyright: © 2021 Sociedade Portuguesa de Pneumologia Copyright: Copyright 2021 Elsevier B.V., All rights reserved.